Kajian pemanfaatan lemak fleshing industri penyamakan kulit - Sutyasmi, Sri (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2011)
The process of fleshing in the leather tannery generates solid waste in theform of pieces of meat mixed with fat. Fleshing wastes contain approximately 50-80 o% protein and 20-40 % fat. Protein from fleshing waste can be used for animal feed, cornpost and gelatin. The fat can be used as a base for soap rnaking, fat liquoring at leather tanning processes, and fuel (diesel oil substitute). This research aimed to study the possibility of utilizing fat fron fleshing waste in leather tannery.The result show that fat offleshing waste could be obtained by heating or by mechanical/enzymatic extraction. Fats obtained from fleshing waste were called tallow that had a triglyceride with unsaturated carboxylic acid and considered to be ester group. Ester group could be reacted with bases by saponification reaction to produce soap. Ta use thefat offleshing waste in leather anointment as fat liquoring, then the fat must be sulfonated. Meanwhile, for the manufacture of enginefuel then fleshing waste fat rnust be compressed, heated, and thenfiltered. For the manufacture of biodiesel thefat must be added with 5% diesel fuel in order to meet the biodiesel standard DIN 5 I 606